2019
DOI: 10.1108/nfs-01-2019-0007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for diabetes mellitus and hypertension among artisans in Ogun state, Nigeria

Abstract: Purpose This study was designed to assess the risk factors associated with hypertension (HTN) and diabetes among artisans in Ogun State, Nigeria. Evidences suggest increasing prevalence, incidences and morbidity of diabetes and HTN in Nigeria. However, the purpose of this study is to plan and prioritize effective intervention programs, there is need to provide data on the prevalence and risk factors for HTN and diabetes among local groups. Design/methodology/approach In total 300 apparently healthy artisans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…The current study showed that the participants aged 41-60 years were found to have significantly higher HbA 1c than the group aged # 40 years. It buttresses the report of some other studies where increment of age, particularly above 40 years, was associated with an elevated level of HbA 1c that is having poor glycemic control (Tokuyama et al, 2008;Harrabi et al, 2014;Camara et al, 2015;Oladoyinbo et al, 2019). But, there are also some studies that found negative or no significant association between poor glycemic control and age of the participants (Adham et al, 2010;Khattab et al, 2010;Yazidi et al, 2016;Mosleh et al, 2017;Tekalegn et al, 2018).…”
Section: Glycemic Controlmentioning
confidence: 60%
“…The current study showed that the participants aged 41-60 years were found to have significantly higher HbA 1c than the group aged # 40 years. It buttresses the report of some other studies where increment of age, particularly above 40 years, was associated with an elevated level of HbA 1c that is having poor glycemic control (Tokuyama et al, 2008;Harrabi et al, 2014;Camara et al, 2015;Oladoyinbo et al, 2019). But, there are also some studies that found negative or no significant association between poor glycemic control and age of the participants (Adham et al, 2010;Khattab et al, 2010;Yazidi et al, 2016;Mosleh et al, 2017;Tekalegn et al, 2018).…”
Section: Glycemic Controlmentioning
confidence: 60%
“…These FFQs included the validated Food and Agricultural Organization FFQ (FAO-FFQ), validated FFQ based on reference values from the International Network of Food Data System and the U.S. Department of Agriculture National Nutrition Database, the SIREN/AWFGEN study FFQ, and the WHO standard 24-h dietary recall questionnaire [13,[36][37][38][39][40]. Of the 10 studies that employed the WHO Stepwise instrument, different combinations of questions to assess the intake of salt, fruits and vegetables, snacks, sweets, fried foods, fats and oils, or alcohol were used (detailed in Table 1) [41][42][43][44][45][46][47][48][49][50][51][52]. Furthermore, 12 studies used either nonpublished or validated structured questionnaires to assess dietary intake [53][54][55][56][57][58][59][60][61][62][63].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Nowadays, prevailed chronic non-communicable diseases such as diabetes, cardiovascular diseases, cancers and stroke have been attracting more attention in health-care systems (Payahoo et al, 2014;Nawamawat et al, 2020). Reducing the burden of chronic diseases is a priority in health-care systems (Bhardwaj et al, 2018;Oladoyinbo et al, 2019). Modifying lifestyle factors such as self-care management education, nutrition interventions to healthy eating, increasing physical activity, periodically screening of patients and determining main modifiable risk factors of chronic diseases can be considered as efficient approaches to achieving the goals (WHO, 2016;American Diabetes Association, 2017).…”
Section: Introductionmentioning
confidence: 99%